(untitled) (Eureka Journal of Health Sciences & Medical Innovation, 2026)
The hemostasis system in newborns is a unique dynamic system that functions in a state of physiological immaturity and alternative balance, which makes it extremely vulnerable to disorders associated with abnormalities in gestational age. The purpose of this work is a comparative analysis of the state of the coagulation and platelet links of hemostasis in premature and post-term newborns. Based on the analysis of modern scientific literature (review), it was found that premature newborns demonstrate pronounced hypocoagulation (a significant decrease in the levels of most coagulation factors and natural inhibitors) and functional inferiority of platelets, which causes a high risk of hemorrhagic complications, primarily intraventricular hemorrhage. At the same time, disorders in post-term newborns are often associated with chronic placental dysfunction and asphyxia, which can shift the balance towards hypercoagulability or the secondary development of disseminated intravascular coagulation (DIC) syndrome against the background of severe perinatal pathology. Thus, knowledge of the specific features of hemostasis is critically important for adequate laboratory monitoring and timely correction of coagulopathies in neonatal practice.